2017
DOI: 10.1007/s15010-017-1049-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastroenteritis in primary care: a longitudinal study in the Swiss Sentinel Surveillance Network, Sentinella

Abstract: PurposeAcute gastroenteritis (AG) leads to considerable burden of disease, health care costs and socio-economic impact worldwide. We assessed the frequency of medical consultations and work absenteeism due to AG at primary care level, and physicians’ case management using the Swiss Sentinel Surveillance Network “Sentinella”.MethodsDuring the 1-year, longitudinal study in 2014, 172 physicians participating in “Sentinella” reported consultations due to AG including information on clinical presentation, stool dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Since we report rates of patients who visited their PCP, we expect the proportion of colonoscopy/FOBT to be higher than among the general popula- Strengths of this study include the high adherence of PCPs in the Sentinella network, some of whom have participated in the network for over 30 years. The Network routinely collects nationwide and country representative patient data and has participated in several studies (Gnadinger et al 2017;Hurlimann et al 2015;Schmutz et al 2017), so Sentinella physicians are practiced in providing quality data. The data collection form was developed and tested with PCPs, and was based on a comprehensible algorithm that limited the amount of data PCPs needed to collect, and standardized data collection between PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Since we report rates of patients who visited their PCP, we expect the proportion of colonoscopy/FOBT to be higher than among the general popula- Strengths of this study include the high adherence of PCPs in the Sentinella network, some of whom have participated in the network for over 30 years. The Network routinely collects nationwide and country representative patient data and has participated in several studies (Gnadinger et al 2017;Hurlimann et al 2015;Schmutz et al 2017), so Sentinella physicians are practiced in providing quality data. The data collection form was developed and tested with PCPs, and was based on a comprehensible algorithm that limited the amount of data PCPs needed to collect, and standardized data collection between PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…A more precise proportion could be estimated by an epidemiologically based survey of general practitioners on their diagnostic and billing behavior. The results of a longitudinal study from Switzerland show that GPs do not routinely obtain laboratory diagnostic evidence in cases of gastroenteritis [31]. Experiences within this study show, however, that such projects are not easy to conduct.…”
mentioning
confidence: 79%
“…Of the few studies reporting on how often antimicrobial drugs are prescribed for acute gastroenteritis, estimates range from 8.5% of 2,089 cases in a sentinel surveillance sample from primary care in Switzerland in 2014 ( 12 ) to 65% in a survey of 237 physicians in China in 2012 ( 13 ). Our results were most similar to the estimates reported from the Switzerland study, which also found that antimicrobial drugs were more likely to be prescribed for older patients and those with fever ( 12 ).…”
Section: Discussionmentioning
confidence: 99%